Association between waist-hip ratio and subclinical myocardial injury in the general population: Insights from the NHANES - Wang, Zhenwei; Huang, Xu; Li, Jingjie; Liu, Naifeng; Wei, Qin (Frontiers in Endocrinology, 2022)
Background and aims: Although studies have shown that higher waist-hip ratio (WHR) is closely related to higher risk of metabolism-related diseases, the relationship between WHR and subclinical myocardial injury (SC-MI) is unknown. This study was to evaluate the effect of WHR on SC-MI in the general population free from cardiovascular disease. Methods and results: The cross-sectional study included 6253 participants without cardiovascular disease (CVD) from the third National Health and Nutrition Examination Survey (NHANES III) for further analysis. Restricted cubic spline, multivariable logistic regression models and subgroup analyses were performed to assess the association between WHR and SC-MI. The multivariate logistic regression showed that after adjusting for potential confounding factors, participants in the higher quartiles had higher risk of developing SC-MI than those in the first quartile of WHR [Q3, OR (95% CI): 1.523 (1.159, 2.000), P = 0.002; Q4, OR (95% CI): 1.719 (1.279, 2.311), P < 0.001], and this relationship was robust among the participants aged ≥ 50 years, with hypertension and without diabetes. Every 0.1 unit increase in WHR, as a continuous variable, increased the risk of SC-MI by more than 20% [OR (95% CI): 1.233 (1.092, 1..392), P = 0.001]. And restricted cubic spline analysis showed that there was a linear positive correlation between WHR and the risk of SC-MI. Conclusions: WHR may be an independent risk factor for SC-MI in the general population free from CVD.